Using E- Mind Mapping Strategy in Developing EFL Middle School Students’ Vocabulary Use and Metalinguistic Awareness Skills - Ahmed Abdel Hamid, Eman (International Journal of Psychosocial Rehabilitation, 2022)
This study purpose was to investigate the effect of E-mind mapping strategy on vocabulary use and metalinguistic awareness skillsof middle School Students. To accomplish the purpose of the study, the quasi- experimental designwas adopted.Participants wereforty (40) students at AbdelWahab Elgoharymiddle School, Egypt. The participants were allocated in two groups. The treatment group was taught using E-mind mapping strategymeanwhile the control one was taught by the old-style method in the first semester of the scholastic year 2019- 2020. The experiment sustained for ten (10) weeks in which the instruments of thestudy were implemented to examine the impact of E-mind mapping strategy. The outcomes were statistically analyzed by SPSS. The results revealed that there were statistically significant differences at (α = 0.05) between the mean scores of the control group and those of the treatment one on the vocabulary use and metalinguistic awareness posttest in favor of the treatment group. This positive result was attributed to the effect of using the E-mind mapping strategy. According to the findings, the researcher recommends that EFL teachers need to activate E-mind mapping strategy throughout teaching vocabulary to develop their students‟vocabulary useandmetalinguistic awareness skills.